Simulation of FIB‐SEM Images for Analysis of Porous Microstructures. Issue 3 (22nd August 2012) - Prill, Torben; Schladitz, Katja
Summary Focused ion beam nanotomography‐scanning electron microscopy tomography yields high‐quality three‐dimensional images of materials microstructures at the nanometer scale combining serial sectioning using a focused ion beam with SEM. However, FIB‐SEM tomography of highly porous media leads to shine‐through artifacts preventing automatic segmentation of the solid component. We simulate the SEM process in order to generate synthetic FIB‐SEM image data for developing and validating segmentation methods. Monte‐Carlo techniques yield accurate results, but are too slow for the simulation of FIB‐SEM tomography requiring hundreds of SEM images for one dataset alone. Nevertheless, a quasi‐analytic description of the specimen and various acceleration techniques, including a track compression algorithm and an acceleration for the simulation of secondary electrons, cut down the computing time by orders of magnitude, allowing for the first time to simulate FIB‐SEM tomography. SCANNING 35: 189‐195, 2013. © 2012 Wiley Periodicals, Inc.